Pelatihan Pengembangan Pembelajaran Bahasa Indonesia Berbasis Pendekatan Teaching At The Right Level (Tarl) Bagi Guru Sekolah Dasar Di Kabupaten Bantul - Setiawan Edi Wibowo; Ali Mustadi; Supartinah Supartinah; Septia Sugiarsih; Octavian Muning Sayekti; Mita Saputri (Pusat Riset dan Inovasi Nasional, 2025)
Elementary school teachers in Kretek District, Bantul Regency, face various challenges in implementing the Teaching at the Right Level (TaRL) approach in Indonesian language learning, even though the Independent Curriculum emphasizes the importance of recognizing the diversity of individual student abilities. This community service activity aims to provide training to teachers on the TaRL concept and assist them in developing Indonesian language learning tools based on this approach. The activity was carried out through a series of stages, including workshops, mentoring, implementation, and evaluation involving elementary school teachers in Kretek District. Data were collected through pre-tests, post-tests, questionnaires, and observations. The results of the activity showed an increase in teachers' understanding of the concept and application of TaRL, as indicated by an increase in the average score from 62.3 in the pre-test to 84.7 in the post-test. In addition, the teachers successfully developed TaRL-based learning modules and media. Based on the results of the evaluation questionnaire, 86% of participants stated that the training was very useful, 78% felt more confident in implementing TaRL in the classroom, and 72% hoped for further mentoring. Thus, this training has proven effective in improving elementary school teachers' competency in understanding and implementing the TaRL approach in Indonesian language learning and providing practical solutions to differences in student ability in the classroom.